Analisis Kesediaan Membayar pada Hotel Syariah Di Daerah Istimewa Yogyakarta - Muhammad Abdul Aziz; Unggul Priyadi (CV. Syntax Corporation Indonesia, 2021)
Sharia hotel with halal services and product that have various advantages and are safer for consumers. Consumers are willing to pay for sharia hotel lodging services compared to conventional hotels at a certain price level. This study aims to analyze the value of the willingness to pay of consumers and the factors that influence it at sharia hotel in Special Region of Yogyakarta. The method used in this research is quantitative research. The research sample was 94 respondent using purposive sampling. The research data was sourced from direct and online questionnaries from sharia hotel guests period of 2019-2020. This study using contingent valuation analysis with open ended question to measure the value of willingness to pay and multiple regression with ordinary least square to test the hypothesis. The results show that the average value of WTP at sharia hotels in Yogyakarta is IDR 545,479. WTP value is greater than the rate offered by sharia hotel management in Yogyakarta. Factors that influence WTP at sharia hotel in Yogyakarta are religiosity and facilities. The variables of religiosity and facilities have a significant positive affect, while tourism motivation, knowledge, brand/image, and service do not affect WTP.